Exploring Freshmen’s Insight on Physics Measurement Uncertainty: Voices from the General Physics Course - Mahdiannur, Muhamad Arif (JURNAL PENDIDIKAN SAINS (JPS), 2024)
Since secondary school, students have always learned measurement accuracy. Understanding measurement uncertainty is crucial, as is acquiring, handling, and analyzing measurement data. This study investigates first-year students’ knowledge of measurement uncertainty in physics. This study utilized a one-group pre- and post-test design within a teacher research or self-study framework. This study involved 25 participants from an educational program at a university in East Java, Indonesia. The focus in this study was on four categories: (a) “repeated distance” (RD), (b) “using repeats” (UR), (c) “same mean different spread” (SMDS), and (d) “different mean same spread” (DMSS), based on Pollard et al.’s new codebook for the Physics Measurement Questionnaire. We observed moderate normalized gain in most of the four criteria following the lecture intervention. We also conducted a paired t-test and found statistical differences before and after the intervention. These results show freshmen struggle with understanding uncertainty in physics measurement based on their secondary schools’ experiences, highlighting the need for a learning intervention combining theory and laboratory practice. These findings underscore the importance of enhancing education for future science teachers in secondary schools.